MORAL REASONING INTERNAL AUDITOR, DUKUNGAN MANAJEMEN SENIOR, DAN MOTIVASI TERHADAP EFEKTIVITAS AUDIT INTERNAL DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI - Sari, Dewi Puspa (Universitas Muhammadiyah Palembang, 2021)
The problem of this research is an Effect of Moral Reasoning Internal Auditor, Senior Management Support, and Motivation of the Effectiveness of Internal Audit with Organizational Culture as Moderating Variables (An Empirical Study of State-Owned Enterprise Non Banking at Palembang South Sumatera). This type of research is associative research. The data used are primary and secondary data. The population in this study is an internal auditor in the State-Owned Enterprise total of 40 respondents. Data collection techniques by using interviews and questionnaires. Methods of data analysis used in this research is the analysis of qualitative and quantitative analysis. Results showed that Moral Reasoning of the auditors, Senior Management Support, and Motivationsignificantly positively influence the effectiveness of Internal Audit. Organizational Culture moderate the moral reasoning internal auditor as a pure moderator of the Effectiveness of Internal Audit, Organizational Culture moderate the Senior Management Support as pure moderateof the Effectiveness of Internal Audit and Organizational Culture moderate Motivation of the Effectiveness of Internal Audit.